Pemanfaatan Pekarangan Dengan Tanaman Obat Keluarga (Toga) di MI Muhammadiyah Unggulan Suruh Kalang, Jaten, Karanganyar - Ima Aryani; Lintang Indah Cahyani; Lolita Yosi Kusumaningrum (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2023)
The MI Muhammadiyah Unggulan Suruhkalang has a yard that is still empty. The yard can be used to plant family medicinal plants (TOGA). TOGA is a plant that has medicinal properties in healing and preventing disease. This dedication can indirectly instill independent character in students. Students are expected to be able to cultivate medicinal plants that can be used as first treatment before going to health services. This service aims to provide knowledge about the use of empty yards around schools and how to cultivate family medicinal plants (TOGA) and increase awareness and enthusiasm in developing the use of TOGA independently. The method used is training, which consists of socialization, demonstration and mentoring. This service activity was attended by all 80 students. The result of this service activity is an increase in students' knowledge and independence in TOGA cultivation.